Techniques for managing data flows in information communication nets - Kosenko, V. (НТУ «ХПИ», 2019)
The paper deals with the issues of increasing the efficiency of data processing in information communications nets of critical infrastructure systems (CIS ICN). The method for adaptive control of data flow distribution is proposed. A set of parameters is divided into subsets of basic and variable control parameters. Variable parameters can be the content of tasks, users, the request rate, capabilities of the equipment.